Easy-to-clean coating material and preparation method thereof
By combining silanized carbon nanotubes loaded with nano zinc oxide with inorganic silicate system, a cross-linking network structure is formed, which solves the problem of difficulty in cleaning the inner wall of the oven, achieves high hydrophilicity and easy cleaning, and is suitable for the inner wall of the oven. Preparation of layer materials.
Patent Information
- Application Number
- CN202411782985.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing coating is difficult to clean the inner wall of the oven, which causes oil stains to remain and may corrode the oven, and has poor easy cleaning performance.
Using silanized carbon nanotubes loaded with nano zinc oxide as superhydrophilic functional components, the cross-linking network structure is formed through acidification treatment and dodecyl triethoxysilane modification, which improves the dispersion and affinity of carbon nanotubes. Water-based and combined with the inorganic silicate system to form a rough three-dimensional structure, enhancing the hydrophilic self-cleaning properties of the coating.
It achieves good hydrophilicity and easy cleaning of the inner wall of the oven. The coating material is simply prepared at room temperature, has a wide range of application, strong adhesion, impact resistance and easy cleaning.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coatings, and in particular to an easy-to-clean coating material and a preparation method thereof. Background Art
[0002] Since the invention of the oven, there has been a problem that cannot be solved: the difficulty in cleaning the stains on the inner wall. After long-term use, the inner wall of the oven is covered with oil stains. If not handled in time, the residual oil stains may accumulate and eventually corrode the oven, causing irreparable damage to the oven.
[0003] For example, CN103666191B discloses an absorbing coating for an inner partition of a microwave oven and a preparation method thereof, as well as an inner partition of a microwave oven and a microwave oven using the absorbing coating for an inner partition of a microwave oven. The absorbing coating for an inner partition of a microwave oven contains 30 to 55 parts by weight of an epoxy resin, 3 to 4 parts by weight of an epoxy resin curing agent, 20 to 22 parts by weight of an organic solvent, 6 to 8 parts by weight of an inorganic filler, 10 to 15 parts by weight of a pigment, 8 to 10 parts by weight of an absorbing material, and 2 to 3 parts by weight of a coupling agent.
[0004] For example, CN107304320B discloses an organic hydrophilic coating composition, a hydrophilic coating, and aluminum materials for heat exchangers such as pre-coated fin materials, which are used to form a hydrophilic film having self-cleaning properties in addition to long-term hydrophilicity on the surface of various hard materials such as metal materials, plastic materials, and ceramic materials. The organic hydrophilic coating composition contains a polyvinyl alcohol resin as a resin component and a phenol compound as an added component, wherein the phenol compound has two or more hydroxyphenyl groups in the molecule, and each hydroxyphenyl group has a bulky substituent that exhibits a steric hindrance effect on the hydroxyl group.
[0005] However, the easy-to-clean performance of the above coating still needs to be improved, and the present invention is hereby proposed. Summary of the invention
[0006] The purpose of the present invention is to overcome the poor easy-to-clean performance of the coating in the above-mentioned prior art and to propose an easy-to-clean coating material and a preparation method thereof.
[0007] The purpose of the present invention can be achieved by the following technical solutions: The first aspect of the present invention provides an easy-to-clean coating material, comprising the following components by weight: 100 parts of an inorganic silicate solution, 5-10 parts of a filler, 0.5-2 parts of a dispersant, 0.5-2 parts of a defoamer, 0.5-2 parts of a leveling agent, 10-20 parts of a super-hydrophilic functional component, and 20-60 parts of deionized water; The super-hydrophilic functional component is silanized carbon nanotube loaded with nano zinc oxide.
[0008] Preferably, the preparation method of the super-hydrophilic functional component comprises the following steps: S1, adding dodecyltriethoxysilane to a mixture of water, ethanol and isopropanol, stirring evenly to obtain a dispersion, adding carbon nanotubes to a mixture of sulfuric acid and nitric acid for a primary reaction, then adding the dispersion for a secondary reaction, filtering and drying to obtain modified carbon nanotubes; S2, under inert gas, the modified carbon nanotubes and nano zinc oxide are mixed and ball milled to obtain a super-hydrophilic functional component.
[0009] Preferably, in step S1, the volume ratio of dodecyltriethoxysilane, water, ethanol and isopropanol is 1:(0.5-1):(0.5-1):(0.5-1).
[0010] Preferably, in step S1, the ratio of the carbon nanotubes, nitric acid and sulfuric acid is 1 g: (50-100) ml: (150-300) ml.
[0011] Preferably, in step S1, the first reaction step is to stir the reaction at 80-120° C. for 4-8 h, and the second reaction step is to reflux at 100-150° C. for 1-3 h.
[0012] Preferably, in step S2, the inert gas is nitrogen or argon.
[0013] Preferably, in step S2, the mass ratio of the modified carbon nanotubes to nano zinc oxide is 1:(1-3), and the particle size of the nano zinc oxide is 40-80 nm.
[0014] Preferably, in step S2, the specific conditions of the ball milling are: 200-400 r / min ball milling for 3-6 h.
[0015] Preferably, the inorganic silicate solution is selected from a sodium silicate aqueous solution having a modulus of 1.0-6.0 or a potassium silicate aqueous solution having a modulus of 1.0-6.0.
[0016] Preferably, the inorganic silicate solution is an aqueous solution of sodium silicate with a modulus of 6.
[0017] Preferably, the filler is one of causticized calcium carbonate, titanium dioxide and titanium dioxide.
[0018] Preferably, the filler is causticized calcium carbonate.
[0019] Preferably, the dispersant is one or more of polycarboxylic acid sodium salt, polyacrylate potassium salt, and polyacrylate sodium salt.
[0020] Preferably, the defoamer is a higher alcohol defoamer or a silicone defoamer.
[0021] Preferably, the leveling agent is a polyether siloxane copolymer.
[0022] The second aspect of the present invention provides a method for preparing the easy-to-clean coating material, comprising the following steps: Add the inorganic silicate solution, super-hydrophilic functional component and water into the reactor, stir evenly, then add filler, dispersant, defoamer and leveling agent in sequence, disperse at room temperature for 4-10 hours to obtain an easy-to-clean coating material.
[0023] The third aspect of the present application provides the use of the easy-to-clean coating material in an oven.
[0024] Compared with the prior art, the present invention has the following beneficial effects: 1. Compared with the prior art, the self-cleaning coating obtained by the present invention has good hydrophilic properties when applied to an oven, making the oven easy to clean, and its preparation method is simple, the easy-to-clean coating material can be prepared at room temperature, and has a wide range of applications.
[0025] 2. Compared with the prior art, the present invention firstly performs oxidation treatment on the carbon nanotubes, and acidifies the carbon nanotubes through the action of sulfuric acid and nitric acid, so that the hydroxyl and carboxyl groups on the outer surface of the carbon nanotubes increase greatly, and improve their dispersibility and hydrophilicity in the inorganic silicate system, and their particle size is small, the specific surface area is large, the surface energy is high, and it is easy for other substances to react with each other. In addition, the acidification also removes the related impurities of the carbon nanotubes, and does not change the structure of the carbon nanotubes themselves. On the other hand, by modifying carbon nanotubes with dodecyltriethoxysilane, the hydroxyl groups on the surface of the carbon nanotubes react with silane for modification, and the hydrolysis and condensation of the silane groups will produce a cross-linked network structure, which is beneficial to the interface binding of nano-zinc oxide and carbon nanotubes, and dodecane will produce an inter-steric hindrance effect, which reduces the van der Waals force. The reason for the agglomeration of carbon nanotubes is that the van der Waals force is large. The spatial steric hindrance effect of dodecane is used to reduce the van der Waals force, which naturally enhances the dispersibility of the modified carbon nanotubes, thereby enhancing the dispersibility of the loaded nano-zinc oxide in the inorganic silicate system. Therefore, the chemical action of dodecane and the physicochemical action produced by adsorption synergistically greatly improve the dispersion of the carbon nanotubes. Therefore, the dispersibility makes a large number of hydroxyl groups dispersed in the inorganic silicate system to improve the hydrophilicity, and the inorganic silicate has excellent permeability and can penetrate into the zinc oxide and form an alternating -O-Si-O-polysiloxane network through the condensation reaction of sodium silicate, so that the nano zinc oxide particles are firmly embedded in the siloxane network, which not only improves the interface interaction between the nano zinc oxide oxygen and forms a rough structure, but also further forms a rough three-dimensional structure of inorganic silicate-nano zinc oxide-modified carbon nanotubes, which further enhances the hydrophilicity. Therefore, the coating formed in this way has excellent super hydrophilic self-cleaning properties. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below in conjunction with specific embodiments.
[0027] For ease of understanding of the present application, the present application will be described more fully below by way of embodiments. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0028] For simplicity, the present application only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unclearly recorded range; and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, although not clearly recorded, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. It should be noted that, unless otherwise stated, the term "and / or" used herein includes any and all combinations of one or more related listed items, and "above", "below" include the number, and the meaning of "multiple" in "one or more" is more than two. Example 1
[0030] This embodiment provides a method for preparing an easy-to-clean coating material, comprising the following steps: Preparation of super-hydrophilic functional components: S1, adding dodecyltriethoxysilane to a mixture of water, ethanol and isopropanol, wherein the volume ratio of dodecyltriethoxysilane, water, ethanol and isopropanol is 1:0.5:0.5:0.5, stirring to obtain a dispersion, adding 1 g of carbon nanotubes to a mixture of 50 ml of sulfuric acid and 150 ml of nitric acid and stirring at 100° C. for 6 h, then adding the dispersion and refluxing at 120° C. for 1 h, filtering and drying to obtain modified carbon nanotubes; S2, under inert gas, the modified carbon nanotubes and nano zinc oxide with a particle size of 50 nm are mixed, wherein the mass ratio of the modified carbon nanotubes to the nano zinc oxide is 1:1, and ball milling is performed at 300 r / min for 4 hours. After ball milling, a super hydrophilic functional component is obtained.
[0031] Preparation of easy-to-clean coating materials: An inorganic sodium silicate solution with a modulus of 4, 15 parts of super hydrophilic functional components and 30 parts of deionized water are added to the reactor and stirred evenly. Then, 8 parts of causticized calcium carbonate, 1 part of sodium polycarboxylate dispersant, 1 part of high carbon alcohol defoamer and 1 part of polyether siloxane copolymer are added in sequence and dispersed at room temperature for 8 hours to obtain an easy-to-clean coating material. Example 2
[0032] This embodiment provides a method for preparing an easy-to-clean coating material, comprising the following steps: Preparation of super-hydrophilic functional components: S1, adding dodecyltriethoxysilane to a mixture of water, ethanol and isopropanol, wherein the volume ratio of dodecyltriethoxysilane, water, ethanol and isopropanol is 1:0.5:0.5:0.5, stirring to obtain a dispersion, adding 1 g of carbon nanotubes to a mixture of 50 ml of sulfuric acid and 150 ml of nitric acid and stirring at 100° C. for 6 h, then adding the dispersion and refluxing at 120° C. for 1 h, filtering and drying to obtain modified carbon nanotubes; S2, under inert gas, the modified carbon nanotubes and nano zinc oxide with a particle size of 50 nm are mixed, wherein the mass ratio of the modified carbon nanotubes to the nano zinc oxide is 1:1, and ball milling is performed at 300 r / min for 4 hours. After ball milling, a super hydrophilic functional component is obtained.
[0033] Preparation of easy-to-clean coating materials: Add an inorganic sodium silicate solution with a modulus of 6, 18 parts of super hydrophilic functional components and 38 parts of deionized water into a reactor and stir evenly. Then add 8 parts of causticized calcium carbonate, 1 part of sodium polycarboxylate dispersant, 1 part of high carbon alcohol defoamer and 1 part of polyether siloxane copolymer in sequence and disperse at room temperature for 8 hours to obtain an easy-to-clean coating material. Example 3
[0034] This embodiment provides a method for preparing an easy-to-clean coating material, comprising the following steps: Preparation of super-hydrophilic functional components: S1, adding dodecyltriethoxysilane to a mixture of water, ethanol and isopropanol, wherein the volume ratio of dodecyltriethoxysilane, water, ethanol and isopropanol is 1:0.5:0.5:0.5, stirring to obtain a dispersion, adding 1 g of carbon nanotubes to a mixture of 50 ml of sulfuric acid and 150 ml of nitric acid and stirring at 100° C. for 6 h, then adding the dispersion and refluxing at 120° C. for 1 h, filtering and drying to obtain modified carbon nanotubes; S2, under inert gas, the modified carbon nanotubes and nano zinc oxide with a particle size of 50 nm are mixed, wherein the mass ratio of the modified carbon nanotubes to the nano zinc oxide is 1:1, and ball milling is performed at 300 r / min for 4 hours. After ball milling, a super hydrophilic functional component is obtained.
[0035] Preparation of easy-to-clean coating materials: An inorganic sodium silicate solution with a modulus of 3, 12 parts of super hydrophilic functional components and 28 parts of deionized water are added to the reactor and stirred evenly. Then, 8 parts of causticized calcium carbonate, 1 part of sodium polycarboxylate dispersant, 1 part of high carbon alcohol defoamer and 1 part of polyether siloxane copolymer are added in sequence and dispersed at room temperature for 8 hours to obtain an easy-to-clean coating material. Example 4
[0036] This embodiment provides a method for preparing an easy-to-clean coating material, comprising the following steps: Preparation of super-hydrophilic functional components: S1, adding dodecyltriethoxysilane to a mixture of water, ethanol and isopropanol, wherein the volume ratio of dodecyltriethoxysilane, water, ethanol and isopropanol is 1:0.5:0.5:0.5, stirring to obtain a dispersion, adding 1 g of carbon nanotubes to a mixture of 50 ml of sulfuric acid and 150 ml of nitric acid and stirring at 100° C. for 6 h, then adding the dispersion and refluxing at 120° C. for 1 h, filtering and drying to obtain modified carbon nanotubes; S2, under inert gas, the modified carbon nanotubes and nano zinc oxide with a particle size of 50 nm are mixed, wherein the mass ratio of the modified carbon nanotubes to the nano zinc oxide is 1:3, and ball milling is performed at 300 r / min for 4 hours. After ball milling, a super-hydrophilic functional component is obtained.
[0037] Preparation of easy-to-clean coating materials: An inorganic sodium silicate solution with a modulus of 4, 15 parts of super hydrophilic functional components and 30 parts of deionized water are added to the reactor and stirred evenly. Then, 8 parts of causticized calcium carbonate, 1 part of sodium polycarboxylate dispersant, 1 part of high carbon alcohol defoamer and 1 part of polyether siloxane copolymer are added in sequence and dispersed at room temperature for 8 hours to obtain an easy-to-clean coating material.
[0038] Comparative Example 1 This comparative example provides a method for preparing an easy-to-clean coating material, comprising the following steps: Preparation of super-hydrophilic functional components: S1, adding 1g of carbon nanotubes to a mixture of 50ml of sulfuric acid and 150ml of nitric acid and stirring at 100°C for 6h, then adding the dispersion and reflux at 120°C for 1h, filtering and drying to obtain a solid phase; S2, under inert gas, the solid phase and nano zinc oxide with a particle size of 50 nm are mixed, wherein the mass ratio of the solid phase to the nano zinc oxide is 1:1, and ball milling is performed at 300 r / min for 4 hours. After ball milling, a super hydrophilic functional component is obtained.
[0039] Preparation of easy-to-clean coating materials: An inorganic sodium silicate solution with a modulus of 4, 15 parts of super hydrophilic functional components and 30 parts of deionized water are added to the reactor and stirred evenly. Then, 8 parts of causticized calcium carbonate, 1 part of sodium polycarboxylate dispersant, 1 part of high carbon alcohol defoamer and 1 part of polyether siloxane copolymer are added in sequence and dispersed at room temperature for 8 hours to obtain an easy-to-clean coating material.
[0040] Comparative Example 2 This comparative example provides a method for preparing an easy-to-clean coating material, comprising the following steps: Preparation of super-hydrophilic functional components: Adding dodecyltriethoxysilane to a mixture of water, ethanol and isopropanol, wherein the volume ratio of dodecyltriethoxysilane, water, ethanol and isopropanol is 1:0.5:0.5:0.5, stirring to obtain a dispersion, adding 1 g of carbon nanotubes to a mixture of 50 ml of sulfuric acid and 150 ml of nitric acid and stirring at 100° C. for 6 h, then adding the dispersion and refluxing at 120° C. for 1 h, filtering and drying to obtain a superhydrophilic functional component; Preparation of easy-to-clean coating materials: An inorganic sodium silicate solution with a modulus of 4, 15 parts of super hydrophilic functional components and 30 parts of deionized water are added to the reactor and stirred evenly. Then, 8 parts of causticized calcium carbonate, 1 part of sodium polycarboxylate dispersant, 1 part of high carbon alcohol defoamer and 1 part of polyether siloxane copolymer are added in sequence and dispersed at room temperature for 8 hours to obtain an easy-to-clean coating material.
[0041] Comparative Example 3 This comparative example provides a method for preparing an easy-to-clean coating material, comprising the following steps: Preparation of easy-to-clean coating materials: An inorganic sodium silicate solution with a modulus of 4, 15 parts of nano zinc oxide with a particle size of 50 nm and 30 parts of deionized water are added to a reactor and stirred evenly. Then, 8 parts of causticized calcium carbonate, 1 part of sodium polycarboxylate dispersant, 1 part of high carbon alcohol defoamer and 1 part of polyether siloxane copolymer are added in sequence and dispersed at room temperature for 8 hours to obtain an easy-to-clean coating material.
[0042] Comparative Example 4 This comparative example provides a method for preparing an easy-to-clean coating material, comprising the following steps: Preparation of easy-to-clean coating materials: An inorganic sodium silicate solution with a modulus of 4, 15 parts of nano-silica with a particle size of 50 nm and 30 parts of deionized water are added to the reactor and stirred evenly. Then, 8 parts of causticized calcium carbonate, 1 part of sodium polycarboxylate dispersant, 1 part of high carbon alcohol defoamer and 1 part of polyether siloxane copolymer are added in sequence and dispersed at room temperature for 8 hours to obtain an easy-to-clean coating material.
[0043] Test Case The compositions of Examples 1 to 4 and Comparative Examples 1 to 4 were applied onto a metal substrate and cured to obtain a coating.
[0044] 1. Adhesion test Test method: Use a blade or a grid cutter to make 100 small squares with a spacing of 1mm on the coating in a criss-cross pattern, scratching deep into the metal substrate and removing the burrs on the scratches. Cover the scratched area with adhesive tape (brand 3M 610 or Yongda) at a 45° angle along the 100 grids, flatten the tape so that there are no bubbles between the tape and the coating, pull the two ends of the tape, and quickly peel off the tape at a 90° angle to the surface of the test plate. No coating will fall off. Repeat three times.
[0045] 2. Impact resistance test: Test method: Place the coated specimen on the anvil with the coating facing upwards. The impacted part of the specimen should be at least 15mm away from the edge, and the distance between the edges of each impact point should not be less than 15mm. The heavy hammer (mass 1000±1g) is fixed at a height of 500mm on the slide by the control device. Press the control button and the heavy hammer will fall freely on the punch. Lift the heavy hammer, take out the test plate, and perform impact tests on the same test plate three times at the same impact height. If there is no damage, cracking or shedding of the coating at the impact point on the specimen, it is qualified.
[0046] 3. Water contact angle test The contact angle refers to the angle θ between the tangent of the gas-liquid interface at the intersection of the gas, liquid and solid phases, passing through the liquid and the solid-liquid boundary line. It is a measure of the degree of wettability. If θ<90°, the solid surface is hydrophilic, that is, the liquid is easier to wet the solid. The smaller the contact angle, the more water spreads on the surface of the substrate, and the easier it is to clean. If θ>90°, the solid surface is hydrophobic, that is, the liquid is not easy to wet the solid and is easy to move on the surface.
[0047] 4. Cleaning performance test Apply oil stains to the surface of the coated stainless steel substrate and cure it at room temperature for 10 days. Then wipe it with a rag dipped in clean water and then wipe it dry with a dry rag. If there is no stain residue on the surface, it is recorded as Level 1. If there is a small amount of stain residue on the surface, it is recorded as Level 2. If there is a large amount of stain residue on the surface, it is recorded as Level 3.
[0048] The test results are shown in Table 1 below.
[0049] Table 1 Water resistance and contact angle test results of coatings
[0050] It can be seen from the data in Table 1 that the coating obtained in the embodiment of the present application has excellent hydrophilicity, strong adhesion, qualified impact resistance and easy cleaning compared to the coating obtained in the comparative example. In addition, the preparation method of the easy-to-clean coating material of the present application is simple, can be prepared at room temperature, and can be mass-produced.
[0051] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. An easy-to-clean coating material, characterized in that: The invention comprises the following components by weight: 100 parts of inorganic silicate solution, 5-10 parts of filler, 0.5-2 parts of dispersant, 0.5-2 parts of defoamer, 0.5-2 parts of leveling agent, 10-20 parts of super-hydrophilic functional component, and 20-60 parts of deionized water; The super-hydrophilic functional component is a silanized carbon nanotube loaded with nano zinc oxide. The preparation method of the super-hydrophilic functional component comprises the following steps: S1, adding dodecyltriethoxysilane to a mixture of water, ethanol and isopropanol, stirring evenly to obtain a dispersion, adding carbon nanotubes to a mixture of sulfuric acid and nitric acid for a primary reaction, then adding the dispersion for a secondary reaction, filtering and drying to obtain modified carbon nanotubes; S2, under inert gas, the modified carbon nanotubes and nano zinc oxide are mixed and ball milled to obtain a super-hydrophilic functional component.
2. The easy-to-clean coating material according to claim 1, characterized in that: In step S1, the volume ratio of dodecyltriethoxysilane, water, ethanol and isopropanol is 1:(0.5-1):(0.5-1):(0.5-1); And / or, in step S1, the ratio of the carbon nanotubes, nitric acid and sulfuric acid is 1 g: (50-100) ml: (150-300) ml; And / or, in step S1, the first reaction step is to stir the reaction at 80-120° C. for 4-8 h, and the second reaction step is to reflux at 100-150° C. for 1-3 h.
3. The easy-to-clean coating material according to claim 1, characterized in that: In step S2, the inert gas is nitrogen or argon; And / or, in step S2, the mass ratio of the modified carbon nanotubes to nano zinc oxide is 1:(1-3), and the particle size of the nano zinc oxide is 40-80 nm; And / or, in step S2, the specific conditions of the ball milling are: 200-400 r / min ball milling for 3-6 h.
4. The easy-to-clean coating material according to claim 1, characterized in that: The inorganic silicate solution is selected from a sodium silicate aqueous solution with a modulus of 1.0-6.0 or a potassium silicate aqueous solution with a modulus of 1.0-6.
0.
5. The easy-to-clean coating material according to claim 1, characterized in that: The inorganic silicate solution is a sodium silicate aqueous solution with a modulus of 6.
6. The easy-to-clean coating material according to claim 1, characterized in that: The filler is one of causticized calcium carbonate, titanium dioxide and titanium dioxide.
7. The easy-to-clean coating material according to claim 1, characterized in that: The dispersant is one or more of polycarboxylic acid sodium salt, polyacrylate potassium salt, and polyacrylate sodium salt; And / or, the defoamer is a higher alcohol defoamer or an organosilicon defoamer; And / or, the leveling agent is a polyether siloxane copolymer.
8. A method for preparing an easy-to-clean coating material according to any one of claims 1 to 7, characterized in that: The following steps are involved: Add the inorganic silicate solution, super-hydrophilic functional component and water into the reactor, stir evenly, then add filler, dispersant, defoamer and leveling agent in sequence, disperse at room temperature for 4-10 hours to obtain an easy-to-clean coating material.
9. Use of the easy-to-clean coating material according to any one of claims 1 to 7 in an oven.
Citation Information
Patent Citations
Microwave-absorbing coating for microwave oven inner partition and its preparation method; microwave oven inner partition and microwave oven.
CN103666191B
Organic hydrophilic coating compositions, hydrophilic films, and aluminum materials for heat exchangers
CN107304320B
High-pressure-resistant polypropylene plastics for automobile engine igniter shell
CN108034128A
Bio-based super-hydrophobic and anti-icing coating and construction method
CN109762453A
Hydrophilic easy-to-clean coating and preparation method and application thereof
CN111040486A
Cited By
Antibacterial modified polypropylene material and preparation method thereof
CN120888138A